2007
DOI: 10.1007/s00213-007-0982-x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of ethanol and nicotine on learning in C57BL/6J mice depend on both dose and duration of treatment

Abstract: Objective and rationale-Alcohol and nicotine are commonly co-abused; one possible explanation for co-abuse is that each drug ameliorates the aversive effects of the other. Both drugs have dose-dependent effects on learning and memory. Thus, this study examined the interactive effects of acute ethanol and acute, chronic, or withdrawal from chronic nicotine on fear conditioning in C57BL/6J mice.Materials and methods-Conditioning consisted of auditory conditioned stimulus-foot-shock unconditioned stimulus pairing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 55 publications
4
49
2
Order By: Relevance
“…Some studies have shown that foreground conditioning results in stronger conditioning [62,77], while other studies have not found this effect [15,5,43,51,60,61]. Although no differences in freezing to the context were found between background and foreground conditioning in the current study, previous work in our lab has demonstrated that there are differences in the effects of foreground and background conditioning that are visible at one week, but not at 24 hours, post-training [32]. This and other evidence suggests that differences do exist in the neural mechanisms that underlie foreground and background contextual fear conditioning.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Some studies have shown that foreground conditioning results in stronger conditioning [62,77], while other studies have not found this effect [15,5,43,51,60,61]. Although no differences in freezing to the context were found between background and foreground conditioning in the current study, previous work in our lab has demonstrated that there are differences in the effects of foreground and background conditioning that are visible at one week, but not at 24 hours, post-training [32]. This and other evidence suggests that differences do exist in the neural mechanisms that underlie foreground and background contextual fear conditioning.…”
Section: Discussioncontrasting
confidence: 75%
“…Although animal models have been used to examine the somatic and affective symptoms of nicotine withdrawal, less research has focused on the effects of nicotine withdrawal on learning and memory. One behavioral paradigm that has been used to examine the effects of nicotine on learning and memory is contextual fear conditioning [see 31 for review], and studies have consistently shown that acute nicotine enhances contextual conditioning, chronic nicotine does not alter contextual conditioning and nicotine withdrawal disrupts contextual conditioning [16,13,15,32,64,65].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine-induced sensitization is a mechanism that is thought to underlie craving and risk for relapse to smoking [27]. Interestingly, exposure to alcohol attenuated the nicotine withdrawal signs, similar to reports by Gulick and Gould, who found that ethanol reversed nicotine withdrawal symptoms [56]. Thus, alcohol might have a protective effect against nicotine withdrawal.…”
Section: Effect Of Nt69l On Nicotine Withdrawalsupporting
confidence: 73%
“…A considerable body of evidence suggests a solid interaction between ethanol and nicotine in the central nervous system (Collins et al 1993(Collins et al , 1996Smith et al 1999;Lê et al 2003) in which the nicotinic acetylcholine receptors seem to have an important role for such interrelation (3,15,16).Former reports have indicated that the combination of alcohol and nicotine may produce state-dependent learning in humans (17). In addition, according to some later studies, the administration of nicotinic receptor agonists reversed the ethanol-induced amnesia in laboratory animals (7,(18)(19)(20).While nicotine may reverse the ethanol-induced amnesia (similar to pre-test ethanol), the drugs have some opposite effects on other cognitive functions (6,8,21). Where nicotine enhances learning either through a direct effect on attention or affecting the pre-synaptic nicotinic acetylcholine receptors, ethanol may potentially impair learning (4)(5)(6).…”
Section: Introductionmentioning
confidence: 95%